Determinan Preferensi Pembelian Iphone Pada Generasi Z: Peran Fear Of Missing Out (FOMO) Dan Media Sosial - Zuraidah Zuraidah; Madona Khairunisa; Nurhikmah Nurhikmah (Sharing: Journal of Islamic Economics Management and Business, 2026)
The rapid growth of social media and the phenomenon of Fear of Missing Out (FoMO) have influenced iPhone purchase preferences among Generation Z. This study aims to examine the effects of FoMO and social media on iPhone purchase preferences among students of MAN 2 Pekanbaru City. A quantitative approach with an associative research design was employed. Data were collected through questionnaires administered to 91 respondents and analyzed using multiple linear regression. The results indicate that both FoMO and social media have a positive and significant effect on iPhone purchase preferences and jointly explain 65.0% of the variance in purchase preferences. These findings suggest that psychological factors and social media exposure play a significant role in shaping iPhone purchase preferences. This study is limited to students of MAN 2 Pekanbaru City; therefore, its findings cannot be generalized to the entire Generation Z population in Indonesia. Future research is recommended to include broader and more diverse samples to obtain more representative findings.